Single solvent based film casting method for the production of porous polymer films - Hossain, Kazi M. Zakir; Felfel, Reda M.; Ogbilikana, Prince S.; Thakker, Dhruma; Grant, David M.; Scotchford, C.A.; Ahmed, Ifty (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2018)
A single solvent based film casting process for fabricating porous polymer films was developed in this study. The porous film was produced by mixing concentrated polylactic acid/ chloroform solution (20 wt%) and fresh chloroform solvent followed by film casting. The average pore sizes of the films produced were seen to increase from 2.1 (±0.1) µm to 6.4 (±0.2) µm with increasing ratio of concentrated PLA solution and fresh solvent from 1:2 to 1:4. Functional groups of PLA after casting into porous film were confirmed via Fourier transform infrared (FTIR) spectroscopy analysis. Cytocompatibility studies (via Alamar Blue assessment) utilising MG-63 cells on the porous PLA films revealed an increase in cell metabolic activity up to 8 days post-seeding. In addition, these direct cell culture studies showed that the porous membranes supported cell adhesion and growth not only on the surface but also through the porous structures of the membrane, highlighting the suitability of these porous films in tissue engineering applications.